2012
DOI: 10.1111/j.1744-9987.2011.01056.x
|View full text |Cite
|
Sign up to set email alerts
|

Upper Limb Disability in Hemodialysis Patients: Evaluation of Contributing Factors Aside From Amyloidosis

Abstract: This cross-sectional case-control study evaluated upper limb muscle strength and shoulder mobility in hemodialysis (HD) patients with arteriovenous fistula or graft. Twenty-five adult patients on thrice-a-week HD treatment for 6 months at least, were selected for the study. In all the patients and control subjects, handgrip tests and tests of range of motion in the upper extremities were evaluated by physiotherapy tests. Patients on HD showed lower muscle strength than age and sex matched subjects without seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 21 publications
(18 reference statements)
1
10
1
Order By: Relevance
“…The same study also found that complications related with upper extremities were more significant in the extremity having fistula [12]. Contrary to this, in a recent study by Soyupek et al, upper extremity complication prevalence was found as similar in dialysis patients receiving treatment by HD method and peritoneal dialysis patients without vascular access [13].…”
Section: Discussioncontrasting
confidence: 39%
See 1 more Smart Citation
“…The same study also found that complications related with upper extremities were more significant in the extremity having fistula [12]. Contrary to this, in a recent study by Soyupek et al, upper extremity complication prevalence was found as similar in dialysis patients receiving treatment by HD method and peritoneal dialysis patients without vascular access [13].…”
Section: Discussioncontrasting
confidence: 39%
“…We believe that the said contradiction in study results were related to the variable assessing tools. In a study conducted by Capitani et al, only the differences in strength and range of motion were evaluated while conducting assessments concerning upper extremities [12]. Our evaluations were more towards methods assessing upper extremity functionality.…”
Section: Discussionmentioning
confidence: 99%
“…A survey completed by 100 hemodialysis patients revealed that fatigue on dialysis days and fatigue on nondialysis days were reported by 67% and 40% of patients, respectively, as being barriers to physical activity (29). The enforced immobility associated with the dialysis treatment may lead to muscle dysfunction (30), while others have found that hemodialysis treatment is associated with higher levels of arm disability (31,32).…”
Section: Dialysis-related Factors That May Contribute To Functional Dmentioning
confidence: 99%
“…The possible effect of AVF or graft presence on upper extremity motor function is an understudied question. Preservation of upper extremity motor function and dexterity may be a crucial issue for an elderly end‐stage renal disease patient deciding about the future AV access especially since there seems to be a general propensity to hand dysfunction in HD patients due to factors like dialysis related amyloidosis , greater prevalence of diabetic neuropathy/vasculopathy , and perhaps obligate arm position during HD treatments . In 1988 Branz and Newton studied 30 maintenance HD patients and they found a 2 kg weaker handgrip strength (HGS) in vascular access hands compared to the contralateral side .…”
mentioning
confidence: 99%
“…The differences were larger in longer‐term HD patients and the authors concluded that both the chronicity of renal failure and the presence of vascular access contribute to deterioration in hand function. A subsequent study of similar size (in 25 HD patients) could find no reduction of handgrip strength on the access side but a reduction in the shoulder external rotation range of motion was reported . Since these studies were relatively small and yielded contradictory results, the possible negative effect of the presence of AVF or grafts on the upper extremity motor abilities remains to be clarified.…”
mentioning
confidence: 99%